2022
DOI: 10.1007/s40618-022-01854-y
|View full text |Cite
|
Sign up to set email alerts
|

Development of a prediction score (ThyroCOVID) for identifying abnormal thyroid function in COVID-19 patients

Abstract: Purpose Thyroid dysfunction in COVID-19 carries clinical and prognostic implications. In this study, we developed a prediction score (ThyroCOVID) for abnormal thyroid function (TFT) on admission amongst COVID-19 patients. Methods Consecutive COVID-19 patients admitted to Queen Mary Hospital were prospectively recruited during July 2020–May 2021. Thyroid-stimulating hormone (TSH), free thyroxine (fT4) and free triiodothyronine (fT3) were measured on admission. Multivaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…But what is apparent is that thyroid dysfunction is accompanied with more severe form of COVID thus monitoring TFT seems to be beneficial specially in some populations including patients with preexisting thyroid condition, in severe form of infection, and in patients with manifestation of viral thyroiditis (neck pain). Likewise, regarding to the new published article inventing a scoring system for thyroid dysfunction in COVID patient with five parameters including symptoms, presence of ischemic heart disease/congestive heart failure and abnormal laboratory finding (lymphocyte count, C-reactive protein, and SARS-CoV-2 cycle threshold values) should be considered for TFT evaluation ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…But what is apparent is that thyroid dysfunction is accompanied with more severe form of COVID thus monitoring TFT seems to be beneficial specially in some populations including patients with preexisting thyroid condition, in severe form of infection, and in patients with manifestation of viral thyroiditis (neck pain). Likewise, regarding to the new published article inventing a scoring system for thyroid dysfunction in COVID patient with five parameters including symptoms, presence of ischemic heart disease/congestive heart failure and abnormal laboratory finding (lymphocyte count, C-reactive protein, and SARS-CoV-2 cycle threshold values) should be considered for TFT evaluation ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis of the low T3 group demonstrated that the level of T3 was lower in non-survivors and in those with more severe disease, and our ROC analysis demonstrated that the FT3 level was a acceptable predictor of critical COVID-19. Recent studies of COVID-19 patients also demonstrated an association between lymphopenia and thyroid function ( 32 ), indicating a potential interaction between the hypothalamic-pituitary-thyroid axis and the immune system ( 33 ). The levels of lymphocytes and D-dimer affect the relationship between COVID-19 and the thyroid, because a strong inflammatory response and coagulation dysfunction predict worse clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The key marker of ESS is a predominantly low T3 level, and decreased thyroxine (T4) or thyroid-stimulating hormone (TSH), also called thyrotropin, can be revealed. At the same time, reports underlined the increased frequency of subacute thyroiditis and thyrotoxicosis [4,5].…”
Section: Abstract: Covid-19 Euthyroid Sick Syndrome In Children Infla...mentioning
confidence: 99%
“…Recent studies underlined the association between low thyroid hormones levels, especially FT3, and critical disease as well as increased mortality related to SARS-CoV-2 infection [7]. Despite the presence of much research on adults [5,8], it remains unclear in the pediatric population. A routine thyroid panel study is not indicated for asymptomatic patients with COVID-19.…”
Section: Abstract: Covid-19 Euthyroid Sick Syndrome In Children Infla...mentioning
confidence: 99%